An exploration of the suggested link between thin idealised female images portrayed in magazines and the development of eating disorders amongst adolescent females: a critical review - Parker, Jessica (2012)
The prevalence of eating disorders has increased and currently presents a significant risk to the mental health of young people. Eating disorders have the highest mortality rate of any of the psychiatric conditions and are currently being treated in individuals as young as 12. This has resulted in increasing investigation into the factors which contribute to the onset of eating disorders. A critical review of the literature was undertaken in order to explore the suggested link between thin idealised female images portrayed in magazines and the development of eating disorders amongst adolescent females. 9 studies were analysed in light of three main themes identified. From the studies explored, though it is evident that the suggested link between thin idealised female images portrayed in magazines and the development of eating disorders can potentially have a negative influence on some young adolescent females, this may not be as widespread as first thought. Realistic images which portray all types of body shape and size to be ideal have the potential to have a positive influence on body satisfaction. Furthermore, certain personality traits can act as moderating factors in terms of how influenced an individual becomes.